Physicochemical insights into ammonia-amine blending for CO2 capture: Speciation, ammonia volatilization, salt precipitation, and regeneration energy in aqueous NH3-MEA and NH3-AMP solutions - Sang-Jun Han; Hye-Rin Kim; Jin-Young Kim; Jae-Beom Lee; Gwon-Woo Lee; Jae-Hoon Jeon; Shaukat Ali Mazari; Ung Lee; Jong-Ho Moon (Chemical Engineering Journal, 2026)

Unravelling the Population Genetic Dynamics of the Ivory Snail (Babylonia areolata) in Vietnam: Guiding Sustainable Aquaculture Development - Sang Van Vu; Angkasa Putra; Sarifah Aini; Imon Abedin; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Thanh Tat Le; Hoang Huy Nguyen; Hien Van Doan; In Van Vu; Hyun-Woo Kim; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Genetic diversity and genome-wide association study of horticultural traits in pumpkins (Cucurbita moschata) originating from East Asia - Eun Su Lee; Yoon Jeong Jang; Ye-Rin Lee; Oakjin Lee; Hee-Bum Yang; Hye-Eun Lee; Koeun Han; Do-Sun Kim (Horticulture, Environment, and Biotechnology, 2026)

Cascade energy alignment and absorption enhancement via a guest donor strategy for efficient ternary organic solar cells - Ha Rin Kim; Jinwoong Hong; Donghwan Yun; Hyeseon Shin; Mihyun Kim; Youngchae Cho; Seungmin Baek; Gwangyong Shin; Guanchao Chen; Seyeong Song; Seonghun Lee; Tae Joo Shin; et al. (Chemical Engineering Journal, 2026)

Mitogenomic Characterization and Phylogenetic Insights of the Ornamental Sail-Fin Molly (Poecilia velifera) in Non-Native Indonesian Waters - Sarifah Aini; Rina; Sinar Pagi Sektiana; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Muhammad Hilman Fu’adil Amin; Won-Kyo Jung; Angkasa Putra; I Nyoman Suyasa; Shantanu Kundu; Hyun-Woo Kim (Biochemical Genetics, 2026)

Human adipose-derived stem cell exosomes alleviate human respiratory system-related cells damaged by exposure to SO2 derivatives - Ji-Seon Lee; You-Rin Kim; Dogeon Yoon; Ji Hye Park; Ga Eun You; Wook Chun (Journal of Biosciences, 2025)

Identification of the endangered species Haplotropis brunneriana (Insecta: Orthoptera) from South Korea using exuviae - Mannyun Kim; Hye-Rin Lee; Jong Eun Lee; Deokjea Cha (Journal of Insect Conservation, 2024)
Most Pamphagidae species are at risk of being endangered due to their flightlessness, low mobility, and small habitat range. For the same reason, Haplotropis brunneriana (Orthoptera: Pamphagidae) has been designated an endangered species in South Korea. Endangered species with small populations are difficult to observe and investigate because any damage or disturbance to them are prohibited. To address these problems, we first performed non-invasive genomic DNA (gDNA) extraction using exuviae to identify H. brunneriana . Second, we tested the limit of detection of gDNA in the exuviae and how long it could persist when exposed to artificial environmental conditions. Using exuviae, we identified cytochrome b as a species-specific marker of H . brunneriana that could distinguish them from other grasshoppers with sufficient specificity. In the limit of detection test, gDNA could persist and be amplified from exuviae for up to 40 days. Our results demonstrated that fewer than 10 days is recommended for amplifying gDNA from exuviae to obtain reproducible results. In conclusion, this non-invasive identification method using exuviae can be used as an alternative to species identification when it is difficult to find H. brunneriana in the habitat and has the advantage of allowing genetic research to be conducted without harming the endangered species.

Enzymatic characterization of sucrose phosphorylase from Bifidobacterium dentium: The initial enzyme in the cascade reaction - Hye-Rin Lee; Ye-Jin Kim; Chang-Young Lee; Sang Gil Lee; Tae Gyu Nam; Cheon-Seok Park; Dong-Ho Seo (Food Bioscience, 2024)

Multi-functional energy conversion by strongly coupled Ag3PO4/ZIF-67 heterostructures - Harshavardhan Mohan; Sethumathavan Vadivel; Suhwan Yoo; Ga Hyeon Ha; Gitae Kim; Hye Rin Lee; Han-Kyu Choi; Taeho Shin (Journal of Environmental Chemical Engineering, 2024)

Cobalt–molybdenum–selenide nanoflowers for bifunctional visible light photocatalysis - Harshavardhan Mohan; Ga Hyeon Ha; Gitae Kim; Hye Rin Lee; Hakju Lee; Kyoungsoo Kim; Taeho Shin (Chemosphere, 2023)

Environmental Effects of the Technology Transition from Liquid–Crystal Display (LCD) to Organic Light-Emitting Diode (OLED) Display from an E-Waste Management Perspective - Ji-Min Yeom; Hye-Jin Jung; Soo-Yeong Choi; Dae Sung Lee; Seong-Rin Lim (International Journal of Environmental Research, 2018)

Transcriptome analysis of the threatened snail Ellobium chinense reveals candidate genes for adaptation and identifies SSRs for conservation genetics - Se Won Kang; Bharat Bhusan Patnaik; So Young Park; Hee-Ju Hwang; Jong Min Chung; Min Kyu Sang; Hye Rin Min; Jie Eun Park; Jiyeon Seong; Yong Hun Jo; Mi Young Noh; Jong Dae Lee; et al. (Genes & Genomics, 2018)

Efficacy of a bleomycin microneedle patch for the treatment of warts - Ha Ryeong Ryu; Hye-Rin Jeong; Hye-Seung Seon-Woo; Jung Soo Kim; Seul Ki Lee; Hee Joo Kim; Jin Ok Baek; Jung-Hwan Park; Joo Young Roh (Drug Delivery and Translational Research, 2018)